Price and affordability of direct-acting antiviral regimens for hepatitis C virus in the United States - Rosenthal, Elana S. (Infect Agent Cancer, 2016)
Hepatitis C virus is a serious infection causing cirrhosis, liver cancer, and death. The recent development of direct-acting antivirals has dramatically improved tolerability of treatment and rates of cure. However, the high price of these medications has often limited access to care and resulted in rationing of medications in the United States to those with advanced liver disease, access to specialist care, and without active substance use. This review assesses the way pharmaceutical prices are established and how pricing of directly acting antiviral regimens in the United States has impacted access to treatment for hepatitis C virus.